The superb programme vol.1 - Jarman, Derek (Roma : Raro Video, 2004)
Contains: Glitterbug(1994), Pirate Tape (1982), TG: Physic Rally in Heaven (1980-1981)
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Jarman, Derek